Effects of different treatment measures on the efficacy of diabetic foot ulcers: a network meta-analysis - OuYang, Hong; Yang, Jing; Wan, Haiyan; Huang, Jiali; Yin, Yifan (Frontiers in Endocrinology, 2024)
Introduction Through a network meta-analysis, we compared different treatment measures for patients with diabetic foot ulcers (DFU), assessing their impact on the healing of DFU and ranking them accordingly. Methods We searched the PubMed, the China National Knowledge Infrastructure (CNKI), Embase, the WanFang and the WeiPu database. The retrieval time was from database establishment to January 2024, and retrieval entailed subject and free words. Randomized controlled trials (RCTs) with different treatment measures for DFU were included. Data extraction and evaluation were based on the PRISMA guidelines. Meta-analyses using pairwise and network methods were employed to compare and rank the effectiveness of different treatments for DFU. Results Ultimately, we included 57 RCTs involving a total of 4,826 patients with DFU. When it comes to ulcer healing rates, compared to standard of care(SOC),platelet-rich plasma(PRP), hyperbaric oxygen therapy(HBOT), topical oxygen therapy(TOT), acellular dermal matrix(ADM), and stem cells(SCs) in both direct meta-analysis(DMA) and network meta-analysis(NMA) can effectively increase the complete healing rate. For Scs+PRP, a statistically significant improvement was only observed in the NMA. Moreover, when compared to the negative pressure wound therapy(NPWT) group, the PRP+NPWT group was more effective in promoting the complete healing of ulcers. In terms of promoting the reduction of ulcer area, no statistical differences were observed among various treatment measures. When it comes to ulcer healing time, both PRP and NPWT can effectively shorten the healing time compared to SOC. Furthermore, when compared to the NPWT group, the combined treatment of PRP and ultrasonic debridement(UD) with NPWT is more effective in reducing healing time. In terms of amputation rates and adverse reactions, the PRP group effectively reduced the amputation rate and adverse reactions for patients with DFU. Additionally, compared to the NPWT group, the combined treatment of PRP and UD with NPWT reduced the incidence of adverse reactions. However, no significant differences were observed among other treatment measures in terms of amputation rates and adverse reactions. The ranking results showed that the efficacy of PRP+NPWT and UD+NPWT in promoting ulcer healing, reducing ulcer area, shortening healing time, decreasing amputation rates and adverse reactions is superior to that of the alone PRP group, NPWT group, and UD group. Conversely, the SOC group demonstrates the least effective performance in all aspects. Conclusion Due to the particularity of the wound of DFU, the standard of care is not effective, but the new treatment scheme has a remarkable effect in many aspects. And the treatment of DFU is not a single choice, combined with a variety of methods often achieve better efficacy, and will not bring more adverse reactions.